2008
DOI: 10.1097/nen.0b013e318163354a
|View full text |Cite
|
Sign up to set email alerts
|

Mortalin: A Protein Associated With Progression of Parkinson Disease?

Abstract: Parkinson disease (PD) is a progressive neurodegenerative disorder that is considered to affect the brainstem at its early stages and other brain regions, including the limbic system and isocortex, in advanced stages. It has been suggested that PD progression is characterized pathologically by the spreading of Lewy body deposition. To identify novel proteins involved in PD progression, we prepared subcellular fractions from the frontal cortex of pathologically verified PD patients at different stages of diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 42 publications
4
69
0
Order By: Relevance
“…Consistent with this role, several studies have shown that mortalin may be implicated in the progression of neurodegenerative and protein aggregation disorders, such as Parkinson and Alzheimer (Burbulla et al 2010;De Mena et al 2009;Deocaris et al 2008;Deocaris et al 2007;Koren et al 2009;Shi et al 2008). Moreover, when mammalian mitochondria are challenged with an imported protein with a strong tendency to form aggregates, the mitochondrial unfolded protein response (mUPR) is activated (Aldridge et al 2007;Zhao et al 2002).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 84%
“…Consistent with this role, several studies have shown that mortalin may be implicated in the progression of neurodegenerative and protein aggregation disorders, such as Parkinson and Alzheimer (Burbulla et al 2010;De Mena et al 2009;Deocaris et al 2008;Deocaris et al 2007;Koren et al 2009;Shi et al 2008). Moreover, when mammalian mitochondria are challenged with an imported protein with a strong tendency to form aggregates, the mitochondrial unfolded protein response (mUPR) is activated (Aldridge et al 2007;Zhao et al 2002).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 84%
“…Proteomics Data Mining for PD-related Proteins/Peptides-Proteomic data were gathered from our previous quantitative PD-related proteomic studies, including a general human CSF profiling (19), two general human midbrain profiling studies (20,21), general human frontal cortex profiling studies of PD progression (22)(23)(24), glycoprotein profiling studies of human CSF and frontal cortex (25), a phosphoprotein profiling of human frontal cortex (unpublished data), glyco-and phospho-protein profiling studies in a MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) monkey model (putamen; unpublished data). A total of 15 data sets were integrated: two on the human CSF proteome, four on the human midbrain (substantia nigra) proteome, six on the human frontal cortex proteome, and the remaining three on the monkey putamen proteome.…”
Section: Methodsmentioning
confidence: 99%
“…Patients-In recent reports, mortalin has been implicated in neurodegenerative diseases, such as Parkinson disease (46,47). However, the implication of mortalin expression with AD has not been elucidated.…”
Section: Mortalin Is Down-regulated In Brain Samples From 3xtg-ad Micmentioning
confidence: 99%